Presence in a Pocket. Phantasms of Immediacy in Japanese Mobile Telepresence Robotics - Timo Kaerlein (communication +1, 2012)
The paper addresses prospects of Japanese mobile telepresence robotics where small anthropomorphic devices are designed to act as intermediaries between remote interlocutors. First, an emic perspective of involved scientists and engineers is presented, focusing on example technologies being developed at the Hiroshi Ishiguro Lab in Kyoto (Japan), particularly a "cellphone-type tele-operated android [...] transmitting human presence“ called Elfoid. It represents an attempt to get “behind the veil of the machine” (Sekiguchi/Inami/Tachi 2001, about their RobotPHONE prototype which uses a similar concept) in that it is supposed to act as a solid substitute for a dialog partner through evoking a feeling of presence (sonzaikan in Japanese philosophy, the feeling that someone is sharing the same physical space). In such undertakings, specific utopian ideals of communication become apparent. Paradoxically, the high-tech developments aim at constituting seemingly immediate interactions, preferably bypassing any potentially troublesome interface. The existence of a phantasm of immediacy (Bolter/Grusin 2000) can be traced back to decisive moments in media history and belongs to the central promises of new technological interfaces. Interestingly, the engineers’ statements reveal a latent technophobia, an ambition to overcome the limitations of physical devices altogether and to move on to more direct means of communicative exchange (including the mythical dimension of telepathy). Two questions are of particular concern: 1. On what different levels does the notion of immediacy operate? Not only does it refer to a spiritual ideal of unmediated communion, but it also influences practical decisions in interface design. “Natural” and “Tangible” User Interfaces are the result of a practice of disguise in that they mask their factual hypermediacy to allow for a seamless knotting up of real and mediated environments. 2. What is the relationship between media and the immediate? The concept of immediacy has so far been met with an almost univocal intellectualist disdain on the part of media theorists. The reason for this rejection is simple enough: If one takes ideas of immediacy serious, the self-image of a whole field of study is called into question. The paper thus attempts to provide a contribution to the question of how media build on notions of immediacy. Any theoretical attempt at describing their operations should take into account the intricate relationship between media and the immediate. Note: Download statistics restarted from zero effective January 1, 2024. Please follow this link to see cumulative download statistics from our previous publishing platform: CPO Download Statistics 2012 - 2023
Keywords: Media Theory; Telepresence; Robotics; Mobile Phones; Japan; Immediacy; Elfoid; Hiroshi Ishiguro